Empowering Autochthonous Peoples in Honduras : The Nuestras Raices (Our Roots) Program - Traa-Valarezo, Ximena; Rodríguez, Jorge (World Bank, Washington, DC, 2012)
The Nuestras Rais Program (NR) was created in Honduras in 1995 after massive ethnic demonstrations, in which people protested poor access to basic public services and demanded more access roads (and land rights). The government responded with the Roads for Production (Caminos para la Produccion) program, which paid nominal wages to beneficiaries to open and rehabilitate small tertiary roads and paths. NR phases I and II was financed with domestic funds disbursed through mayors. Most beneficiaries were Lenca of the ONILH federation, the rest belonged to four other federations. NR's main goal is to improve the living conditions of Honduras' nine ethnic groups by helping build human capital, social and cultural assets, and gender equity. NR finances small-scale social and economic infrastructure projects identified, selected, and implemented by community groups.